2009
DOI: 10.2134/jeq2008.0378
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Gypsum Applied to Grass Buffer Strips on Reducing Soluble P in Surface Water Runoff

Abstract: The threat of P transport from land applied manure has resulted in water quality concerns. Research was conducted to evaluate gypsum as a soil amendment applied to grass buffer strips for reducing soluble P in surface runoff. A simulated concentrated flow was created in an established tall fescue (Festuca arundinacea Schreb.) pasture. Poultry litter (PL) was applied at a rate of 250 kg N ha(-1) to the upper 3.05 m of each plot, while gypsum was applied at rates of 0, 1, 3.2, and 5.6 Mg ha-1to the lower 1.52 m … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 31 publications
(32 reference statements)
4
38
0
Order By: Relevance
“…A particularly short-duration effect was reported by Watts and Torbert (2009) who observed about 20% reduction in DRP concentration as a result of gypsum amendment during an initial 30 minute concentrated flow event applied immediately following a poultry litter application and gypsum amendment to a set of test plots. These workers conducted a second 30 minute runoff event four weeks later and found that DRP concentration was highest (4.3 mg l -1 ) in runoff from the plot that had received the highest amount of gypsum dressing.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…A particularly short-duration effect was reported by Watts and Torbert (2009) who observed about 20% reduction in DRP concentration as a result of gypsum amendment during an initial 30 minute concentrated flow event applied immediately following a poultry litter application and gypsum amendment to a set of test plots. These workers conducted a second 30 minute runoff event four weeks later and found that DRP concentration was highest (4.3 mg l -1 ) in runoff from the plot that had received the highest amount of gypsum dressing.…”
Section: Discussionmentioning
confidence: 81%
“…Other plots supplied runoff with DRP concentrations similar to those of the unamended control (3.1-3.3 mg l -1 ). The gypsum amendment did not apparently reduce DRP in concentrated runoff after one month from the application (Watts and Torbert, 2009). …”
Section: Discussionmentioning
confidence: 96%
“…Gypsum's solubility allows movement of Ca and S through the soil profile into rooting zones (Chen and Dick, 2011). In addition to supplying Ca and S for plant nutrition, gypsum can be used as a soil conditioner to improve physical and chemical properties by promoting better aggregation, increasing water infiltration and movement through the profile, reclaiming sodic soils, mitigating subsoil acidity and Al toxicity (Shainberg et al, 1989), and reducing soluble phosphorus (P) loss from agricultural fields (Table 2; Watts and Torbert 2009).…”
Section: Sustainable Uses Of Fgd Gypsum In Agricultural Systems: Intrmentioning
confidence: 99%
“…Improved rooting of many crops Farina and Channon, 1988, Sumner M.E., 1993, Alcordo and Rechcigl, 1993Shainberg et a., 1982;Wendell and Ritchey, 1996; 6. Control of soluble phosphorus runoff from fields Norton, 2008;Watts and Torbert, 2009;Bryant et al, 2012;Torbert and Watts, 2014;Endale et al, 2014. been conducted using mined gypsum. Given FGD gypsum's availability and its smaller and more uniform particle size than commercially mined gypsum, this synthetic source may provide greater soil improvement benefits.…”
Section: Objective and Rationale For The Special Collectionmentioning
confidence: 99%
“…Phosphorus-sorbing filters and denitrifying bioreactors provide ways to trap and treat nutrients in water at and below field edges. Research has been undertaken to evaluate the potential of industrial byproducts (e.g., water treatment residuals, flue-gas-desulfurization gypsum) to sorb P and limit its losses (Ippolito et al 2011;Watts and Torbert 2009). Vegetative buffers can slow runoff velocity and trap sediment and particulate P, but significant fractions of P in runoff are in dissolved form.…”
Section: Summary Of Progressmentioning
confidence: 99%